(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Libraries are considered the most important achievements of the Arab Islamic civilizatation because of their important role in spreading science among Muslims, and their impact on Europe that sunk into darkness. With the establishment of the Fatimid state in Egypt in 358/969, the Fatimids tried to compete with Baghdad in the cultural field by encouraging private and public libraries. Despite of the collapse of the Fatimid state, the books of its libraries remained preserved in the libraries of civilizations that followed, such as the Fadilia and Bimaraston Qaloun Schools.